Effect of Nitrogen and Phosphorous on the Biomass Production of Phyllanthus amarus at Nursery Stage - Tomar, Anita; Chamoli, Rashmi; Singh, V. R. R. (Indian Forester, 2010)
Phyllanthus amarus is an important medicinal plant commonly known as Bhumyamalaki, belongs to family Euphorbiaceae. In the nursery raised seedlings of P. amarus nitrogen and phosphorus treatments were applied as: T0 Control, T1, 30 kg N/ha,T2, 40 kg N/ha, T3, 50 kg N/ha, T4, 30 kg N +50 kg P/ha, T5, 40kgN +50kgP/ha,T6,50kgN +50kgP/ha. The best results were recorded in T4 (N30âˆ—P50) treatments as compared to others. The plants treated with N30âˆ—P50 had highest plant height, number of branches, collar diameter, fresh and dry weight of shoot andhighest biomass.